Gambaran Pengelolaan Keuangan Para Pelaku Umkm di Tengah Pandemi Covid-19: (Studi Kasus Pelaku UMKM Area Jembatan Suramadu Bangkalan) - Septiana, Aldila; Novitasari, Anindita Trinura (Jurnal Pendidikan Ekonomi (JUPE), 2021)
The financial management of MSME actors is a major problem in developing MSMEs towards financial independence. The challenges during the COVID-19 pandemic are getting more complete along with the weak financial management of MSME actors. The purpose of this study is to describe and analyze an overview of the financial management of MSME actors in the midst of the COVID-19 pandemic, especially the Bangkalan Suramadu Bridge area. This study uses a qualitative research method with a qualitative descriptive approach and the type of phenomenological research. Respondents in the study were MSME actors in the Suramadu Bridge Area, which consisted of Madura Typical Snacks MSMEs, Madurese Knick-knacks MSMEs and Madura Batik Crafts SMEs. Data analysis used qualitative data analysis with the stages of data reduction, data presentation, and drawing conclusions/verification. The results show that the financial management of MSME actors in the midst of the COVID-19 pandemic, especially the Bangkalan Suramadu Bridge area, is more selective in controlling sales stock, generating creativity and innovation in various kinds of products sold, and utilizing social media as an online marketing tool in the midst of a pandemic. COVID-19. This is intended so that the income of MSME actors continues to rotate, even though the turnover is not as fast as before the COVID-19 pandemic.